Feasibility Study of Localization and Local Sourcing for Factory-In-A-Box Solution for Contribution to Humanitarian Development in Turkey - Özer, Can; Mandli, Suraj (My University, 2023)
Disasters in today's world result in a significant housing shortage that has a profound impact on the society and countries affected. In addition, those harmed by natural disasters have lost their employment opportunities and economic power. Neighboring nations taking in refugees in camps and settlements from the nations affected by these disasters. Although these camps offer shelter to those in need, it is not always easy or effective for them to integrate into the local population. Localized factory-in-a-box facilities would therefore have a significant impact on how well refugees integrate into society. Additionally, it would be more practical to build portable houses, field hospitals, temporary schools, and other infrastructure. The local population and refugees who are incompetent in terms of skills, education, and language would also make up the labor force in these mobile factories. Therefore, setting up factory-in-a-box facilities in nations that host large numbers of refugees who are willing to work could help build humanitarian settlements. Turkey was chosen as the location for Factory-in-a-Box because of the country's history of natural disasters, demographics, physical infrastructure, and refugee camps. The establishment of a factory-in-a-box solution in Turkey can provide temporary housing and jobs for those affected by the disaster. The localization of a factory-in-a-box in Turkey is made possible by extensive research on variables including incentives, the nation of origin of the brand, and supplier accessibility. After conducting research on localization, industrialists and academics were interviewed to learn more about the difficulties in localizing the bill of materials, including the availability of raw materials, quality and the search for environmentally friendly products, high inflation rates. Finally, a new raw material is recommended by the implementation of the Pugh matrix and the results that were derived.
Keywords: Factory-in-box; Localization; Sourcing; Turkey